Creative Industries In The Polish Economy - Kasprzak, Rafał (Quaestiones Geographicae, 2015)
The paper presents changes in the number of entities in the creative sector in Polish regions between 2009 and 2013. In the analysis use was made of Poland’s Central Statistical Office data to describe the development rate of this sector in the regions.